Brownification reduces oxygen gross primary production and community respiration and changes the phytoplankton community composition: An in situ mesocosm experiment with high‐frequency sensor measurements in a North Atlantic bay. Issue 4 (10th February 2022) - Soulié, Tanguy; Stibor, Herwig; Mas, Sébastien; Braun, Benjamin; Knechtel, Johanna; Nejstgaard, Jens C.; Sommer, Ulrich; Vidussi, Francesca; Mostajir, Behzad
Abstract: In recent decades, the increase in terrestrial inputs to freshwater and coastal ecosystems, especially occurring at northern latitudes, has led to a process of water color darkening known as "brownification." To assess how brownification affects plankton community composition and functioning in northern coastal areas, an in situ mesocosm experiment using a highly colored humic substance to simulate a brownification event was performed in a North Atlantic bay (Hopavågen, Norway) in August 2019. Manual sampling for analyses of nutrient concentrations, phytoplankton pigments and zooplankton abundances was combined with high‐frequency (every 15 min) monitoring of key environmental variables to investigate the response of the plankton community in terms of oxygen metabolism and community composition. In response to brownification, the oxygen gross primary production (GPP) and community respiration (R) slowed down significantly, by almost one‐third. However, GPP and R both decreased to the same extent; thus, the oxygen metabolic balance was not affected. Moreover, the chlorophyll‐ a concentration significantly decreased under brownification, by 9% on average, and the chemotaxonomic pigment composition of the phytoplankton changed, indicating their acclimation to the reduced light availability. In addition, brownification seemed to favor appendicularians, the dominant mesozooplankton group in the mesocosms, which potentially contributed to lowering the phytoplankton biomass. In conclusion, the results of this in situ mesocosm experiment suggest that brownification could induce significant changes in phytoplankton and zooplankton community composition and significantly alter the overall oxygen metabolism of plankton communities in a northern Atlantic bay.